Boosting the electrocatalytic performance of Fe-based perovskite cathode electrocatalyst for solid oxide fuel cells. Issue 13 (October 2021) - Guo, Miaomiao; Xia, Tian; Li, Qiang; Sun, Liping; Zhao, Hui
Abstract: The development of cathode materials with excellent electrocatalytic activity and CO2 tolerance is an important direction for the wide application of solid oxide fuel cells. Herein, the cobalt-free perovskite oxides Bi0.5 Sr0.5 Fe1- x V x O3- δ (BSFV x, x = 0.025, 0.05 and 0.075) are developed as the efficient cathode electrocatalysts for SOFCs. The V-doping strategy is beneficial to improve the thermal stability, CO2 tolerance and electrochemical performance of undoped Bi0.5 Sr0.5 FeO3- δ . Among all samples, Bi0.5 Si0.5 Fe0.95 V0.05 O3- δ (BSFV0.05) cathode presents excellent oxygen reduction reaction activity, achieving a lower polarization resistance of 0.076 Ω cm 2 and the peak power density of the single cell with the BSFV0.05 cathode reaches to 1.16 W cm −2 at 700 °C, which can be comparable to those of the representative cobalt-based cathodes. Furthermore, the improved CO2 tolerance of the BSFV0.05 cathode can be ascribed to the high acidity of the V 5+ and the larger average bonding energy in the oxide.